Qualidade de frutos e sementes de Physalis sp. cultivadas nas condições do semiárido baiano - Barroso, Natália dos Santos (2019)
The genus Physalis exhibits biotechnological potential. Its pleasant taste, diversified use, nutritional and therapeutic value and good performance in hot dry regions have increased cultivation of the fruit in several countries. In order to expand the planting of these fruit trees in Brazil, it is important to understand the influence of soil and climate conditions on the physical and physicochemical traits of the fruits, since environmental conditions during their development have a significant effect on their attributes during maturation, yield and seed vigor. As such, the aim of this study was to monitor the maturation of two varieties (purple and green) of P. ixocarpa and P. peruviana, via physical and physicochemical characterization over the course of their development under the soil and climate conditions of Feira de Santana, Bahia state, Brazil. The physiological quality of the seeds was also assessed during the developmental stages of the fruit. In order to meet the aforementioned objectives, crop field and germination tests were conducted at the Forest Garden (HFUEFS) and Seed Laboratory (LAGER), respectively, of Feira de Santana State University (UEFS). The fruits were collected in different maturation stages and the following traits were assessed: color, fresh weight, length, diameter and total soluble solids. Seeds recently taken from the fruits collected in different maturation stages were assessed for water content and dry weight. After drying for 72 hours at ambient condition, the seed germinability and vigor were determined using the germination test and seedling emergence. Changes in fruit traits follow the same trend over the course of maturation in the two varieties of P. ixocarpa assessed, exhibiting better traits when the calyx is green with dry parts, completely expanded and ruptured. The growing season had a significant effect on fruit traits and seed maturation, and should occur between May and August in Feira de Santana, Bahia. The primary physical and physiological changes in the maturation of P. peruviana fruits occurred up to stage 3. This coincides with the maximum physiological quality of the seeds. However, fruits with the traits required for commercial purposes should be harvested when the fruit and calyx are totally yellow.